Influence Influence Analysis Celebrity Endorsement, Flash Sale, Live Streaming to Impulse Buying Shopee Users in Jember - Indah Respati Kusumasari; Andrias Dwi Mahendrawan; Yanda Bara Kusuma (Universitas KH. Abdul Chalim Mojokerto, 2025)
The digital era is increasingly developing rapidly, e-commerce or electronic commerce has become one of the most widely used and rapidly growing forms of commerce in Indonesia. Quoted to Ramadhan (2020), in the last year, Indonesia managed to rank 3rd in the world in the category of most internet users. Therefore, research about influencing factors impulse buying at platform e-commerce Shopee can provide valuable insights for e-commerce companies and marketers in understanding consumer preferences and needs in Indonesia. Apart from that, this research can also help Shopee to improve their services and attract consumers' interest in continuing to buy products on their platform by optimizing live streaming, and flash sales, but further research still needs to be done to determine the effect celebrity endorsers on impulse buying of platforms. e-commerce Shopee. This research uses a survey and quantitative research method approach. Following the research objectives, this research approach is explorative descriptive, namely research by conducting and providing descriptions of symptoms and phenomena that occur in the field. The results of this research show Celebrity endorsement significant effect on impulse buying Shopee E-Commerce users in Jember City. Flash Sale influential and significant to impulse buying Shopee E-Commerce users in Jember city Live streaming significant effect on impulse buying Shopee E-Commerce users in the city of Jember. And overall, celebrity endorsements, flash sales, and live streaming have a significant effect on impulse buying.